Comparative clinical evaluation of a local drug delivery of cranberry and garcinia fruit gel with tetracycline fibers for amelioration of periodontitis: A split mouth study - Vandana Panda; Pragya Patidar; Rajesh Gaikwad; Shrutika Borad; Lynette Fernandes (Wolters Kluwer Medknow Publications, 2023)
Background: The present study formulates and evaluates a polyberry gel comprising extracts of cranberry (Vaccinium macrocarpon) and brindle berry (Garcinia cambogia) in patients suffering from chronic periodontitis. Materials and Methods: The polyberry gel was evaluated for various physicochemical parameters, in vitro permeability and stability, and the active phytoconstituents were quantified by High-performance thin layer chromatography (HPTLC). Total phenolic content, total antioxidants, and ascorbic acid were estimated in the two extracts by in vitro assays. Patients suffering from chronic periodontitis with probing pocket depth (PPD) up to 5 mm were divided into 3 groups of 21 patients each and treated with scaling and root planing (SRP) or SRP followed by subgingival placement of polyberry gel or tetracycline fibers (standard). Plaque Index (PI), Gingival Index (GI), PPD, Clinical Attachment Level (CAL), and the salivary aspartate aminotransferase (AST) and C-reactive protein (CRP) levels were recorded at baseline and after 1 month. Results: A significant (P < 0.01) reduction in the periodontic disease parameters was observed in the standard and gel-treated groups between their baseline and 1-month time-interval readings. The polyberry gel treatment significantly (P < 0.05 for AST and P < 0.01 for the rest) attenuated the periodontitis-elevated PI, GI PPD, CAL, AST and CRP levels when compared with SRP at the end of the study and was comparable with tetracycline. Conclusion: The amelioration of periodontitis and gingival inflammation may be attributed to the potent antioxidant activity of the polyphenolic phytoconstituents of the gel. The polyberry gel may thus be used as a safe adjunct to SRP/tetracycline in chronic periodontitis.